(untitled) (Research Announcements "Heritage BG", 2025)
Written sources and interdisciplinary analysis provide evidence for the existence of peculiarities in the diet of ancient Thracians, including abstinence for a limited period of time (fasting?) or a complete ban on the consumption of certain foods. In some cases, documented food taboos draw a line between the general population and small isolated groups who have the privilege of eating differently. The information about the food that the Thracians refuse / restrict or are forbidden to accept could reveal more about their cultural identity and self-determination. It is even possible for certain social groups and classes to declare themselves through the food they do not consume. The existing special dietary regimes of the Thracians and their neighbors – Greeks and Scythians – could even be considered as an ethno-distinctive marker for the different nations of the Balkans. References: Bayrakov 2014: Bayrakov, Dimitar. Planinski svetilishta v Yuzhna Trakiya. PhD Dissertation, Faculty of History, Sofia University ‘St. Kliment Ohridski’. Sofia. Galabova, Atanasova 2018: Galabova, Borislava, Nadezhda Atanasova. Antropologichen analiz na kostni ostanki, otkriti v arheologicheski obekti ot Balgariya. Razkopki 2015 g. – Interdistsiplinarni izsledvaniya, No. 25, 5-38. Georgieva 1999: Georgieva, Rumyana. Hrana i hranene (kraya na ІІ-І hil.pr.n.e.) Etnologiya na trakite. In: Etnologiya na trakite (eds. Rumyana Georgieva, Tosho Spiridonov, Mariya Reho). Sofia, 71-111. Georgieva 2005: Georgieva, Rumyana. Kanichka ot Karnobat s izobrazheniya na trakiyski voyn. - Arheologiya, No. 1/4, 32-40. Katincharova 2003: Katincharova, Daniela. Grob na voyn ot elinisticheskata epoha pri Tsrancha Arheologiya No. 44/4, 5-13. Popov 1989: Popov, Dimitar. Zalmoksis. Religiya i obshtestvo na trakite. Sofia. Ribarov, Boev 1997: Ribarov, Georgi, Zlatozar Boev. Kostni ostanki ot divi i domashni zhivotni ot praistoricheskoto selishte „Telish-Redutite“ pri s. Telish (Plevensko). – Historia naturalis bulgarica, No. 7, 61-70. Yordanov, Cholakov 2005: Yordanov, Yordan, Slavcho Cholakov. Antropologichno prouchvane na nekropolite ot zhelyaznata epoha v Isperihska obshtina. In: Helis IV. Izsledvaniya, rezultati i problemi v ‘Sboryanovo’ (ed. Diana Gergova). Sofia, 108-123. Ailincăi 2016: Ailincăi, Sorin-Cristian. Before the Greeks. The Early Iron Age in Dobrudja. In: Prehistoric settlements: social, economic and cultural aspects. Seven studies in the Carpathian area (eds. Florin Gogâltan, Cristina Cordoş). Cluj-Napoca, 201-236. Bartosiewicz 2009: Bartosiewicz, Lászly. A Lion’s Share of Attention: Archaeozoology and the historical record. – Acta Archaeologica, No. 60/1, 275-289. Bianucci, Landini 2007: Bianucci, Giovanni, Walter Landini. Cetacea: An Historical Overview. In: Reproductive Biology and Phylogeny of Cetacea. Whales, Dolphins and Porpoises (ed. Debra Lee Miller). Enfield, NH, 1-33. Davies 1971: Davies, Robert William. The Roman Military Diet. – Britannia, No. 2, 122-142. Dimitrova 2021: Dimitrova, Diana. Zhaba Mogila Cult Complex Near the Town of Strelcha. In: Cinnabar – the Royal Colour in Thracian and Roman Cultures in the Bulgarian Lands (eds. Valeria Fol, Ruja Popova, Rossitsa Manova). Sofia, 126-131. Ekroth 2007: Ekroth, Gunnel. Meat in Ancient Greece: Sacrificial, Sacred or Secular. – Food & History, No. 5/1, 249-272. Finke 2013: Finke, Roger. Origins and Consequences of Religious Restrictions: A Global Overview. – Sociology of Religion, No. 74/3, 297-313. Fol 2020: Fol, Valeria. Thracian Secret Societies. Sofia. Franko, Moore, O’Bryhim, Olson 2001: Franko, George Fredric, Timothy J. Moore, Shawn O’Bryhim, S. Douglas Olson. ‘ACHARNIANS’. In: Greek and Roman Comedy: Translations and Interpretations of Four Representative Plays (ed. Shawn O’Bryhim). Austin, University of Texas Press, 36-82. Haimovici 2003: Haimovici, Sergiu. The Study of the Archaeozoological Remains from Cogealac (Constanţa County) Belonging to the Helenistic Period – Studia Antiqua et Archaeologica, No. 9, 253-260. Jotischky 2011: Jotischky, Andrew. A Hermit’s Cookbook: Monks, Food and Fasting in the Middle Ages. London & New York. Kisyov 2021: Kisyov, Kostadin. Necropolis near Chernozem Village, Plovdiv Region Tumulus No. 1. In: Cinnabar – the Royal Colour in Thracian and Roman Cultures in the Bulgarian Lands (eds. Valeria Fol, Ruja Popova, Rossitsa Manova). Sofia, 42-51. Popova 2021: Popova, Ruja. Tholos Tomb below the Tyulbeto Tumulus Kazanlak. In: Cinnabar – the Royal Colour in Thracian and Roman Cultures in the Bulgarian Lands (eds. Valeria Fol, Ruja Popova, Rossitsa Manova). Sofia, 52-61. Ribarov 1991: Ribarov, Georgi. The Osteological Material from Sunken settlement at Ourdoviza. – Actes du symposium International ‘Thracia Pontica’, No. 4, 113-119. Sallares 1991: Sallares, Robert. The Ecology of the Ancient Greek World. Ithaca, New York, Cornell University Press. Venedikov 1977: Venedikov, Ivan. The Archaeological Wealth of Ancient Thrace. – The Metropolitan Museum of Art Bulletin, No. 35/1, 7-71.